Study on improving collection feeding safety and quality of colostrum for very (extremely) low birth weight infants - Wang, Hua; Li, Qiu-Fang; Xu, Xin-Fen; Hu, Xiao-Li (Frontiers in Pediatrics, 2023)
Objective: This study aims to explore the difficulties related to fresh colostrum feeding for very (extremely) low birth weight infants (VLBWI/ELBWI) and optimize the colostrum administration process. Methods: The VLBWI/ELBWI who were admitted in the neonatal intensive care unit from January to December 2021, were enrolled as the experimental group, and an optimized colostrum feeding process was adopted. The VLBWI/ELBWI admitted from January to December 2020 were enrolled as the control group, and a conventional feeding process was adopted. The general situation of colostrum supply, number of adverse feeding events, maternal breastfeeding rate at the critical time points. Results: Differences in data between the two groups were not statistically significant . In the experimental group, compared with the control group, the time to first colostrum collection was significantly shorter, and the rates of colostrum feeding, and of maternal breastfeeding at 2 weeks after birth and on the day of discharge were significantly higher. Before and after process optimization, the average total time required for the time for nurses to receive the colostrum in the NICU reduced from 7.5 min/time to 2 min/time, and no feeding-related adverse events occurred. Conclusion: Fresh colostrum feeding process optimization for VLBWI/ELBWI, improves the colostrum feeding rate, shortens the time to first colostrum collection, saves the working time of nurses, and improves the maternal breastfeeding rate at key time points.